GATA-3 in Atlantic salmon (Salmo salar): Tissue distribution and its regulation of IL-4/13a promoter - Chi, Heng; Meng, Xianghu; Dalmo, Roy Ambli (Frontiers in Cellular and Infection Microbiology, 2022)
GATA3 is a transcription factor that plays an important role in T cell lineage differentiation and T-helper 2 (Th2) type immune responses. In this study, we developed two rat antibodies against Atlantic salmon GATA-3 (anti-rSsGATA-3a and anti-rSsGATA-3b, respectively). The western blotting and immunofluorescence results showed that anti-rSsGATA-3b antibodies recognized endogenous SsGATA-3 proteins, while the anti-rSsGATA-3a antibodies did not bind SsGATA-3. Immunohistochemical analysis revealed that SsGATA-3 positive cells were detected in all tissues tested, with relatively high number of immune reactive cells in the gills and spleen. Furthermore, the immunohistochemical study revealed that SsGATA-3 was expressed in pillar cells, epithelial cells, chondrocytes, perichondrium cells, and some undifferentiated basal cells. In addition, we determined 577 bp of the upstream promoter sequence of SsIL-4/13a and found four motifs that matched SsGATA-3 binding sites. The promoter regions of SsIL-4/13a were assessed by transfecting four deletion reporter constructs and SsGATA-3 overexpression plasmids. The result showed that SsGATA-3 enhanced the activity of SsIL-4/13a promoters within the region ranging from -317 to -302 bp upstream of the transcriptional start site. Antibodies against Th2 markers such as GATA-3 are valuable in addressing the diversity of T cell responses in fish.